Safety and efficacy of outpatient bronchoscopy in lung transplant recipients - a single centre analysis of 3,197 procedures - Rademacher, Jessica (BioMed Central, 2014)
BACKGROUND: Bronchoscopy represents an important diagnostic and therapeutic tool in the management of lung transplant (LTx) recipients. Outpatient bronchoscopy reduces health costs and may improve quality of life amongst these patients. This retrospective study assessed the safety and efficacy of outpatient bronchoscopy including trans-bronchial biopsy. METHODS: All outpatient bronchoscopies performed on lung transplant recipients between 1 August 2008 and 31 January 2011 were reviewed. Sample quality, duration and complications were recorded. Cost analysis was performed from local trust financial data. RESULTS: A total of 3,197 bronchoscopies were performed on 571 LTx recipients under topical anaesthesia. Fourteen percent of examinations required intravenous sedation. In 79.8% of examinations no complications were observed. Most complications were minor (17.9%) including cough (5.3%) and minimal bleeding after trans-bronchial biopsy (7.8%). Major complications (2.3%) were pneumothorax, severe bleeding and severe desaturation. No attributable deaths were recorded during the observation period. Quality of examination based on bronchoalveolar lavage recovery median (>50%) and biopsy results was adequate at 75% and 77.4%, respectively. Independent risk factors associated with complication were long-term oxygen therapy, sedation before examination, balloon dilatation and transbronchial biopsy. After excluding high-risk procedures annual savings per patient (2.2 bronchoscopies per year) were 2140€. CONCLUSIONS: Outpatient bronchoscopy after LTx is safe. The low complication rate could be attributed to withholding of intravenous sedation. Furthermore, it reduces health community costs.